The role of tumor necrosis factor receptor superfamily in cancer: insights into oncogenesis, progression, and therapeutic strategies - Jiayi Xu (npj Precision Oncology)
Abstract The TNF receptor superfamily (TNFRSF) with extracellular cysteine-rich domains, transmembrane segments, and intracellular signaling motifs, plays crucial roles in cell death, inflammation, growth, and development. These cysteine-rich domains, which are located in the external portion of the TNFRSF, can contain varying numbers of domains, from as few as 1 (as seen in BCMA) to more than 3 (as observed in CD30, DR3), and function as the primary interaction sites for their corresponding ligands from TNFSF. In cancer research, TNFRSF members show abnormal expression across various cancer types, making them potential therapeutic targets. This review focuses on TNFRSF’s structure, biological functions, and significance in cancer. It explores immunotherapeutic applications, targeted drug therapies, and biomarker potential, aiming to offer new perspectives on cancer diagnostics and treatments. However, challenges remain in translating these findings into effective therapies, and further research is needed to overcome these hurdles and improve cancer prognosis.